ANALISIS DAMPAK SUKU BUNGA BI7DRR TERHADAP PROFITABILITAS DAN RISIKO LIKUIDITAS BANK: STUDI EMPIRIS PADA BANK BUKU III DAN IV 2019-2023 - Susan Kalengkongan, Yuliyana; Hasnin, M.; A. Taslim, Fadli; Ekawati, Putri; Nasar, Fahima (Penerbit Lafadz Jaya, 2025)
This study examines the impact of Bank Indonesia 7-Day Reverse Repo Rate (BI7DRR) on profitability (Return on Assets/ROA) and liquidity risk (Loan to Deposit Ratio/LDR) of Kelompok Bank Berdasarkan Modal Inti (KBMI) 3 and 4 banks in Indonesia during 2019-2023 using fixed effect panel data regression (35 observations from 7 purposive banks). Findings reveal BI7DRR negatively and significantly affects ROA (β = -0.45; p < 0.01), more pronounced in KBMI 3 (β = -0.58) than KBMI 4 (β = -0.32), and positively significant on LDR (β = 12.3; p < 0.05) with higher sensitivity in KBMI 3 (β = 15.2). Capital Adequacy Ratio (CAR) positively moderates ROA (+0.02; p < 0.05), while Non-Performing Loan (NPL) exerts strong negative impact (-0.35; p < 0.01). The model satisfies classical assumptions (Adj. R² 0.72 ROA; 0.68 LDR) and sub-period robustness tests. Results confirm the Interest Rate Channel of monetary transmission with bank size heterogeneity, suggesting differentiated macroprudential policies, KBMI 3 hedging strategies, and BI forward guidance.